(untitled) (Third Sector Social Economic Review, 2023)
Considered the future of the Internet, the concept of Metaverse has emerged as one of the most discussed topics in recent years. The metaverse era goes far beyond the traditional Internet with the multidimensional experience it presents however, it brings many uncertainties for companies and consumers. Companies who want to be the first mover are building in Metaverse and promote all their activities. While tech giants are builders, other companies are most likely in the role of participants or content producers. The most functioning Metaverse platforms today are online video games. Developments in the Video Gaming Industry prepared a functioning prototype for Metaverse technologies. Considering the main elements such as virtual worlds, interacting visual representations named avatars, currencies to trade, digital product markets, and social environments, Metaverse platforms are very similar to Massively multiplayer online games. The early audience of Metaverse also consists of new-generation gamers. This study questions the reality of industry expectations by examining Metaverse terms of consumers and companies. The concept of Metaverse is discussed with the evaluations regarding Metaverse marketing practices and target market. In light of the discussions, recommendations are given by considering the academic and practical roadmap of Metaverse.